Enhancing E-Learning Material Creation: Exploring the Practices, Challenges, and Opportunities of the School Learning Resource Quality Assurance Team (SLRQAT) towards TIMER's Information Manuel of Educational Resources Project - John Aris R Trazona; Lustina P Lapie; Consorcia S Tan; Lerma P Buenvinida; Marcial M Bandoy (International Journal of Theory and Application in Elementary and Secondary School Education, 2023)
This study assessed the relationship between the practices, challenges and opportunities among School Resource Quality Assurance Team (SLRQAT) members of City Schools Division of Cabuyao when crafting e-learning materials during the school year 2021-2022. Three hundred ninety-eight (398) public elementary and secondary teachers were the respondents of the study. The researcher utilized the descriptive-correlational research design and self- made questionnaire to assess and measure the variables under study. The statistical tools used to analyze the data gathered were Mean, Standard Deviation, Pearson r and Multiple Linear Regression Analysis. Findings revealed that the profile of the respondents moderate the practices, opportunities and challenges of the SLRQAT members. While, the extent of practices and challenges among SLRQAT were moderated by such profile of the respondents. To ensure a more efficient output, recommendations were suggested based from the findings of the study regarding crafting e-learning materials.